Manipulation of the crystallization of perovskite films induced by a rotating magnetic field during blade coating in air. Issue 9 (12th February 2018) - Lin, Yichuan; Ye, Xiaoqin; Wu, Zhiming; Zhang, Chunquan; Zhang, Yulong; Su, Haifeng; Yin, Jun; Li, Jing
Abstract : A rotating magnetic field (RMF) was employed to manipulate the crystallization of perovskite films during blade coating. Abstract : The blade coating process, which exhibits the merits of rapid film growth and less consumption of materials, has been regarded as a promising method for the fabrication of scalable perovskite films. However, achieving controllable film growth with a high quality is still a challenge. Herein, a rotating magnetic field (RMF) is proposed to manipulate the crystallization of perovskite thin-films during blade coating in air. Improved film quality with good surface coverage and efficient charge transportation has been successfully accomplished in the as-produced smooth, uniform and dense perovskite layers. Thus, an enhanced photovoltaic performance with an average increase of ∼15% in power conversion efficiency was realized in devices configured on the RMF-manipulated perovskite (CH3 NH3 PbI3 ) thin-film when compared with that of the conventional devices. This work well demonstrates a novel strategy to physically manipulate the crystallization of perovskite films with the purpose of a controllable and low-cost fabrication of high performance PSCs.